2021
DOI: 10.1155/2021/5560671
|View full text |Cite
|
Sign up to set email alerts
|

Game Analysis of the Multiagent Evolution of Existing Building Green Retrofitting from the Perspective of Green Credit

Abstract: Existing building green retrofitting can reduce building energy consumption and greenhouse gas emissions, which is conducive to the sustainable development of the construction industry. The financing dilemma of the existing building green retrofitting hinders the large-scale development of green retrofitting in China. This paper establishes the perceived payoff matrix and evolutionary game model of the government, Energy Service Companies (ESCOs), banks, and owners. Through simulation analysis, the primary fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It considers the bounded rationality of the decision-maker and is widely used in many fields [ 38 ]. Chen et al built an evolutionary game model to consider green retrofitting from the perspective of green credit [ 39 ]. Yang used an evolutionary game to analyse the cooperative construction of international transport corridors [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It considers the bounded rationality of the decision-maker and is widely used in many fields [ 38 ]. Chen et al built an evolutionary game model to consider green retrofitting from the perspective of green credit [ 39 ]. Yang used an evolutionary game to analyse the cooperative construction of international transport corridors [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, this study revealed the importance of caring more and providing less punishment ratio to occupant enterprises owing to their vulnerable character. Similarly, Chen et al [89] found that the government exhibits a limited positive behavior to green retrofitting and the feasibility to supply a more professional environment and increasing the awareness of green retrofitting to increase the perceived benefit, which can also be affected in the payoff matrix in the evolutionary game. Although incentives are predicted to be effective for residential buildings located in South Korea and have been confirmed to be synergistic between government and developer groups [11], there are several factors regarding commercial buildings, such as contract cancellation, which prevent developers from adopting a powerful retrofitting level.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of government incentives significantly affected the proportion of ESCO and owners participating in the retrofit. The government increased incentives within a reasonable range, which not only improved the returns of ESCO and owners 32 , 33 , but also solved the financing dilemma of ESCO in GRs 34 . For the lack of ESCO implementation capacity, effective measures to achieve regulatory effectiveness management goals, such as optimization of the government regulatory system, were proposed based on the analysis of key factors affecting the effectiveness of government regulation 35 .…”
Section: Literature Reviewmentioning
confidence: 99%